A theory of economic development. - Ranis, Gustav; Jc, Fei (American Economic Review, 1961)
An attempt is made to make a contribution toward the theory of growth by analyzing the transition process through which an underdeveloped economy hopes to move from a condition of stagnation to one of self sustaining growth. Already accepted ideas are liberally drawn upon before proceeding to weave them into a general explanatory model of economic growth. The analysis begins with an economys first departure from quasistagnation or the initiation of the off Rostow defines this as a period of 2 or 3 decades during which the economy transforms itself in such a way that economic growth becomes subsequently more or less automatic. Its characteristics are a reduction of the rural proportion of the population a doubling of savings rates and the first marked and continuous flowering of industry stimulated by the availability of surplus labor. Arthur Lewis investigates the expansion of the capitalistic or industrial sector as it is nourished by supplies of cheap labor from the subsistence or agricultural sector. Lewis failed to present a satisfactory analysis of the subsistence or agricultural sector. Finally the economy must be able to solve its Malthusian problem if the process of development along a growth path is to prove successful. The contribution of this discussion is to construct a theory of economic growth of which the identified ideas constitute component parts. The 5 sections present the basic structure of the neglected agricultural sector generalize the previously static analysis by admitting the possibility of a change of productivity in the agricultural sector introduce changes in industrial productivity and the concept of a balanced growth criterion by means of which the termination of the take off process is formally defined present a prescise mathematical formulation of the theory which enables the making of certain quantitative conditional predictions as a 1st test of its empirical relevancy and integrate population growth as well as some other real world complexities into the model and investigate the notion of the critical minimum effort in relation to the length of the take off process.